INVOLVEMENT, SATISFACTION AND UNMET NEEDS OF PATIENTS IN ALLAMA IQBAL TEACHING HOSPITAL DERA GHAZI KHAN (The Research of Medical Science Review, 2025)
Objective: The objective of this study was to determine the level of patients’ involvement in healthcare strategies, satisfaction with healthcare services and unmet healthcare needs of patients in a healthcare setting. Study Design: A hospital based cross sectional study. Place and Duration: The study was conducted in Allama Iqbal teaching Hospital Dera Ghazi Khan within a duration of five months. Methods: Patients of age 15-65 years visiting outdoor, emergency, and indoor departments of gynecology, emergency and pediatrics were evaluated for enrollment in this study group during three months from Aug.2024 to Noov.2024. A self-modified questionnaire was used to get data from patients. Data was analyzed by using SPSS Statistic version 27. Mean and standard deviation were calculated for quantitative variables while frequency and percentages were reported for qualitative variables. Chi-square/fisher exact test was applied to determine association between variables. P-value less than 0.05 was considered as significant. Results: The results showed that a majority of respondents (66.2%) indicated that they believe they should be fully informed about their medical conditions. In terms of overall satisfaction with their doctors, a significant portion of respondents rated their doctors positively, with 23.2% considering them excellent, 48.7% above average, and 27% average. However, a small percentage (1.1%) rated their doctors as below average. Satisfaction with doctors' communication skills and expertise varied, with 22.4% very satisfied, 49.8% satisfied, 27% neither satisfied nor dissatisfied, and only 0.8% dissatisfied. These findings suggest overall positive perceptions of hospital facilities, ease of appointment scheduling, and satisfaction with doctors' communication and behavior. Conclusion: We concluded that involvement and satisfaction of patients are essential for better healthcare systems, better decisions and to improve the quality of life of patients.